x-2(x-3)=-4(x-5)

Simple and best practice solution for x-2(x-3)=-4(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-2(x-3)=-4(x-5) equation:


Simplifying
x + -2(x + -3) = -4(x + -5)

Reorder the terms:
x + -2(-3 + x) = -4(x + -5)
x + (-3 * -2 + x * -2) = -4(x + -5)
x + (6 + -2x) = -4(x + -5)

Reorder the terms:
6 + x + -2x = -4(x + -5)

Combine like terms: x + -2x = -1x
6 + -1x = -4(x + -5)

Reorder the terms:
6 + -1x = -4(-5 + x)
6 + -1x = (-5 * -4 + x * -4)
6 + -1x = (20 + -4x)

Solving
6 + -1x = 20 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
6 + -1x + 4x = 20 + -4x + 4x

Combine like terms: -1x + 4x = 3x
6 + 3x = 20 + -4x + 4x

Combine like terms: -4x + 4x = 0
6 + 3x = 20 + 0
6 + 3x = 20

Add '-6' to each side of the equation.
6 + -6 + 3x = 20 + -6

Combine like terms: 6 + -6 = 0
0 + 3x = 20 + -6
3x = 20 + -6

Combine like terms: 20 + -6 = 14
3x = 14

Divide each side by '3'.
x = 4.666666667

Simplifying
x = 4.666666667

See similar equations:

| -13x+x=5x+34 | | 11m+2n-5m+11n= | | 5x+6=3x+30 | | -13x+x=5x+13 | | 4w+8=24 | | -1[7x+6-7(x+1)]=-4x-6 | | w=17 | | 4x-9=3x+9 | | 17x+29y=-7 | | -4*-9=-5-6* | | -10+t=7 | | 4-2|3x=8 | | 4-2|3c=8 | | 4n+12=216 | | 3x^4+5x^3-4x^2-5x-2=0 | | -3b+9=-3b | | 4t+-5t+19t=-18 | | 13x+x=5x+34 | | 3x+7x+2+3=35 | | 7x+12=3x+48 | | 10q-4q-3q=18 | | y+2=30 | | -1|5y=20 | | 3n+3=126 | | 7x+20=3x+76 | | 7x+20+3x+76=180 | | 2x+10-5=25 | | 3x+195+5x+129=180 | | 2x+112+5x+145=180 | | 7.4r+2=-28 | | -x-4=1 | | 3(y+7)=2(y+9)-y |

Equations solver categories